Dichlorido[1-(2-chloroethyl)-3-(pyridin-4-ylmethyl-κN)urea](η6-hexamethylbenzene)ruthenium(II) chloroform monosolvate - Auzias, Mathieu; Süss-Fink, Georg; Therrien, Bruno (My University, 2011)
The RuII atom in the title compound, [RuCl2(C12H18)(C9H12ClN3O)]•CHCl3, exhibits a typical piano-stool coordination, defined by a hexamethylbenzene ligand, two chloride ligands and a pyridylurea ligand coordinated through the pyridine N atom. In the crystal, a dimeric structure is observed due to two strong N-H...Cl interactions between the NH groups of urea and the two chloride ligands of neighbouring molecules. In addition, the C=O group of the urea moiety interacts with the solvent molecule through weak C-H...O interactions.